Development of Science Learning Media Based on Microsoft Power Point on Soil Materials and Structures Earth - Afrida, Yesi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2020)
This research aims to determine the effectiveness of using the development of Microsoft Office Power point-based science learning media on soil and earth structure in class V elementary schools. This research includes development research. In this research, the development design used is the ADDIE (analysis, design, development, implementation and evaluation) development design model. This research produces learning media based on Microsoft Office Power point on soil and earth structure. Based on the research results obtained, (1) Validation results from material experts were 87.3% (very good), (2) Validation results from media experts were 80% (good) (3) Results of interviews with students who said that students enjoyed learning with Using Microsoft Office Power Point based science learning media, it is easier to understand the subject matter, students are active and experience the learning process directly. From the results of this research, it can be concluded that the learning media based on Microsoft Office Power point on soil and earth structure material that was developed is effectively used in the learning process.